Identification of Clinically and Pathophysiologically Relevant Rheumatoid Factor Epitopes by Engineered IgG Targets. Issue 12 (25th October 2020) - Falkenburg, Willem J. J.; Oskam, Nienke; Koers, Jana; van Boheemen, Laurette; Ooijevaar‐de Heer, Pleuni; Verstappen, Gwenny M.; Bootsma, Hendrika; Kroese, Frans G. M.; van Schaardenburg, Dirkjan; Wolbink, Gertjan; Rispens, Theo
Abstract : Objective: Rheumatoid factors (RFs), which are anti‐IgG autoantibodies strongly associated with rheumatoid arthritis (RA), are also found in other diseases and in healthy individuals. RFs bind to various epitopes in the constant (Fc‐) domain of IgG. Therefore, disease‐specific reactivity patterns may exist. This study was undertaken in order to develop a new approach to dissecting RF epitope binding patterns across different diseases. Methods: We analyzed RF reactivity patterns in serum from patients with seropositive arthralgia, patients with RA, and patients with primary Sjögren's syndrome (SS) using bioengineered, natively folded IgG‐Fc targets that demonstrated selective RF binding toward several distinct regions of the IgG‐Fc domain. Results: Rheumatoid factor responses primarily bound the Fc Elbow region, with a smaller number of RFs binding the Fc Tail region, while the Fc receptor binding region was hardly targeted. A restricted reactivity against the IgG‐Fc Tail region was associated with less positivity for anti–citrullinated protein antibodies (ACPAs) and less arthritis development in arthralgia, whereas combined reactivity toward IgG‐Fc Tail and Elbow regions was associated with more arthritis development. Reactivity toward the IgG‐Fc Tail region was observed far more frequently in RA than in primary SS. Conclusion: Bioengineered IgG targets enable serologic characterization of RF reactivity patterns, and use of this approach appears to reveal patterns associated with ACPA detection and arthritis development in patients with arthralgia. These patterns are able to distinguish RA patients from primary SS patients. This new methodology improves the clinical value of RFs and our understanding of their pathophysiologic processes.